2017
DOI: 10.3389/fneur.2017.00440
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus Patients with Comorbid Headaches: The Influence of Headache Type and Laterality on Tinnitus Characteristics

Abstract: BackgroundBoth clinical experience and clinical studies suggest a relationship between tinnitus and headache. Here, we aimed to investigate the influence of comorbid headache type and headache laterality on tinnitus characteristics.MethodThe Tinnitus Research Initiative database was screened for patients of the Tinnitus Center of the University Regensburg who reported comorbid headaches. These patients were contacted to complete additional validated questionnaires. Based on these data, patients were categorize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 42 publications
2
44
2
Order By: Relevance
“…Assuming the severe tinnitus group is the most relevant group to focus tinnitus research on, we may use it to identify co-morbidities shared or distinct between individuals with hyperacusis, headache or TMJ problems. Unlike the previous studies using data from the TRI, where tinnitus with hyperacusis was found comorbid with vertigo, neck pain and TMJ [31], similar to tinnitus with headaches [53], our data indicates that this is not the case (Figure 1). Our results instead suggest that the general assumption that hyperacusis and headaches share similar somatosensory components is wrong.…”
Section: Discussioncontrasting
confidence: 94%
“…Assuming the severe tinnitus group is the most relevant group to focus tinnitus research on, we may use it to identify co-morbidities shared or distinct between individuals with hyperacusis, headache or TMJ problems. Unlike the previous studies using data from the TRI, where tinnitus with hyperacusis was found comorbid with vertigo, neck pain and TMJ [31], similar to tinnitus with headaches [53], our data indicates that this is not the case (Figure 1). Our results instead suggest that the general assumption that hyperacusis and headaches share similar somatosensory components is wrong.…”
Section: Discussioncontrasting
confidence: 94%
“…Patients with migraine have also an increased risk to develop cochlear disorders and in particular tinnitus (Hwang et al, 2018). Langguth et al (2017) described that the laterality and severity of primary headache and tinnitus are significantly related. The co-occurrence of tinnitus and other comorbidities like vertigo, hyperacusis, headache and depression could suggest the presence of a somatoform disorder.…”
Section: Discussionmentioning
confidence: 99%
“…This may affect the composition of the endolymph (i.e., increase of the K + concentration) secreted by the stria vascularis and the dark cells, which may then lead to tinnitus and other disorders (hearing disorders and vertigo; Vass et al., 2001 ). Furthermore, this mechanism may also account for hearing and vestibular disorders that can accompany migraine ( Langguth, Hund, Landgrebe, & Schecklmann, 2017 ; Vass et al., 2001 ).…”
Section: A Pathophysiological Model Of Tttsmentioning
confidence: 99%